Development and validation of ACTYS, an activation analysis code. (September 2017) - Tadepalli, Sai Chaitanya; Kanth, Priti; Indauliya, Gunjan; Saikia, Ishwita; Deshpande, Shishir P.; Subhash, P.V.
Highlights: ACTYS is a nuclear activation solver tailored for fusion activation calculations. Developed and implemented an improved linear chain solver in ACTYS. Mathematical and computational details are presented in this paper Systematic validations and testing are discussed. A short discussion on the computational time is also included. Abstract: It has been well established that rigorous nuclear activation calculations are needed for proper construction, operation and decommissioning of nuclear fusion reactors. Suitable activation codes, which yield accurate results with faster performance yet include all fusion relevant reactions are a pre requisite. ACTYS is a nuclear activation code which has been developed as part of a long term plan of developing a 3-D nuclear activation code. It computes the radioactive/stable inventories formed within materials when exposed to neutron flux through either continuous, pulse irradiation or mixed. ACTYS is based on linear chain solution method for coupled Bateman system. Proper algorithms are needed to ensure that linear chain solver achieves good accuracy with faster performance when coupled to a complicated 3D fusion reactor geometry. The mathematical model and details of computational algorithms are presented in this article. The accuracy and speed of the linear solver are improved by an 'exponential convergence' algorithm and a 'chain weighing' termination technique, that are newly developed and presented here. These two methods lend ACTYS an added edge over typical linear chain solvers. ACTYS primarily utilizes ENDF-6 format condensed neutron data. The code at present form can yield inventories with detailed pathways and radiological parameters such as activity, contact dose, decay heat, gamma source spectra etc. Along with the above, code has a module to classify radiological waste. The classification can be done according to both IAEA criteria (which will be useful for fusion DEMO reactor design) as well as French criteria (used for ITER calculations). The validation tests are performed in an objective pattern starting with the fundamental decay problems. This is followed by a fusion activation solver IAEA benchmarking problem that highlights all the conditions which the code must fulfill. Further, it is tested on realistic fusion machines like ITER. The code is then used for actual ITER radiation waste analysis supplementing further validation. In all the tests, ACTYS results are also compared with a well established code FISPACT-2007 which is at present used for ITER activation calculations widely. The validations are chosen such that almost all fusion-neutron induced nuclear activation reactions are covered. It has been also ensured that properly pulsed long enough activation time scenarios along with proper fusion relevant materials are included in the validation process. Computational performance of ACTYS is also discussed briefly.